A five-day inpatient EMDR treatment programme for PTSD: pilot study. Issue 1 (1st January 2018) - Zepeda Méndez, Mayaris; Nijdam, Mirjam J.; ter Heide, F. Jackie June; van der Aa, Niels; Olff, Miranda
ABSTRACT: Background : Trauma-focused psychotherapies for posttraumatic stress disorder (PTSD) have been demonstrated to be efficacious, but also have considerable non-response and dropout rates. Intensive treatment may lead to faster symptom reduction, which may contribute to treatment motivation and thereby to reduction of dropout. Objective : The aim of the current study was to investigate the feasibility and preliminary effectiveness of an intensive five-day inpatient treatment with Eye Movement Desensitization and Reprocessing (EMDR) and trauma-informed yoga for patients with PTSD. Method : A non-controlled pilot study with 12 adult patients with PTSD was conducted. At baseline the PTSD diagnosis was assessed with the Clinician-Administered PTSD Scale (CAPS-5) and comorbid disorders with the Mini International Neuropsychiatric Interview (MINI). Primary outcome was self-reported PTSD symptom severity (PTSD Check List for DSM-5; PCL-5) measured at the beginning of day 1 (T1), at the end of day 5 (T2) and at follow-up on day 21 (T3). Reliable change indexes (RCI) and clinically significant changes were calculated. Results : From T1 to T3, PTSD symptoms significantly improved with a large effect size (Cohen's d = 0.91). Nine of the 11 patients who completed treatment showed reliable changes in terms of self-reported PTSD. At T3, two of the patients no longer met criteria for PTSD as measured with the PCL-5. One patient dropped out after the first day. No serious adverse events occurred. Conclusions : The majority of patients in our pilot study experienced symptom reduction consistent with reliable changes in this five-day inpatient treatment with EMDR and yoga. Randomized controlled trials – with longer follow up periods – are needed to properly determine efficacy and efficiency of intensive clinical treatments for PTSD compared to regular treatment. This is one of the first studies to show that intensive EMDR treatment is feasible and is indicative of reliable improvement in PTSD symptoms in a very short time frame.